Push : a novel - Sapphire, 1950- (New York : Vintage Contemporaries, 2009)
A self-portrait of a black teenage girl, big, fat, unloved, with a father who rapes her and a jealous mother who screams abuse. For Precious, as she is called, hope appears when a courageous teacher, a young black woman, bullies, cajoles and inspires her to learn to read. By the author of American Dreams.
"Includes the novel Push and a reader's guide"--Cover.
Keywords: Child abuse -- Fiction; Incest -- Fiction; Pregnant teenagers -- Fiction; Literacy -- Fiction; African American girls -- Fiction; African Americans -- New York (State) -- New York -- Fiction; Harlem (New York, N.Y.) -- Fiction; Domestic fiction